Electromagnetic Wave Interactions with 2D Arrays of Single-Wall Carbon Nanotubes. (27th December 2011) - Elwi, Taha A.; Al-Rizzo, Hussain M.
Abstract : We report, for the first time, the scattering, absorption, and reflection characteristics of 2D arrays of finite-length, armchair, single-walled carbon nanotubes (SWNTs) in the visible frequency regime. The analysis is based on the Finite-Element-Method formulation of Maxwell's equations and a 3D quantum electrical conductivity function. Three geometrical models have been considered: solid cylinder, hollow cylinder, and honeycomb. We demonstrate that classical electromagnetic theory is sufficient to evaluate the scattering and absorption cross sections of SWNTs, which revealed excellent agreement against measurements without the need to invoke the effective impedance boundary conditions. The solid and hollow cylindrical models fail to provide accurate results, when both scattering and absorption are considered. Finally, it is shown that reflection and transmission characteristics of both individual and arrays of SWNTs, which are essential for solar cell applications, are strongly influenced by the length and the phenomenological parameters of the SWNT.